Effect of Vitamin D3 (Cholecalciferol) Supplementation on Serum Vitamin D3 and 25-hydroxyvitamin D (25(OH)D) Concentrations Among Participants in the VITAL-DKD Study. (29th May 2020) - Best, Cora; Zelnick, Leila; Hsu, Simon; Limonte, Christine; Thadhani, Ravi; Manson, JoAnn; Sesso, Howard; Boer, Ian de; Hoofnagle, Andrew
Abstract: Objectives: To compare the serum vitamin D3 and 25(OH)D responses to vitamin D3 supplementation in the VITAL-DKD study. Methods: The Vitamin D and OmegA-3 TriaL (VITAL)-DKD was a 2 × 2 factorial, randomized, placebo-controlled trial of vitamin D3 (2000 IU/day) and omega-3 fatty acids (1 g/day) for prevention of chronic kidney disease among adults with type 2 diabetes. For the first 200 enrolled participants, we measured baseline and year 2 serum vitamin D3 concentration with a new validated liquid chromatography-tandem mass spectrometry method. Linear regression was used to test the effects of D3 treatment on changes in serum D3 and 25(OH)D concentrations and to examine possible effect modification by relevant clinical characteristics. Results: Participants were 70 ± 6 years of age, 64% male, 70% non-Hispanic white, and 15% black. At baseline and year 2, serum D3 concentration and 25(OH)D3 concentration were positively related, with a threshold effect at a 25(OH)D3 concentration of 50 nmol/L. Below this threshold, serum D3 concentration rarely exceeded 5 nmol/L. Above it, serum D3 concentration was much more variable. Supplementation increased mean serum D3 concentration from 12 nmol/L at baseline to 41 nmol/L at year 2 (difference compared with placebo 30 nmol/L; 95% CI 25 to 35 nmol/L) and increased mean serum 25(OH)D concentration from 76 nmol/L to 102 nmol/L (difference compared with placebo 33 nmol/L; 95% CI 26 to 40 nmol/L). The effect of treatment on change in serum 25(OH)D was modified by body weight (−0.48 nmol/L per kg of weight; P < 0.01), baseline 25(OH)D concentration (−0.30 nmol/L per nmol/L of baseline 25(OH)D; P < 0.01), baseline D3 concentration (−5 nmol/L per 100% increase in baseline D3 ; P  = 0.04), and non-study vitamin D supplement use (smaller effect as dose of non-study supplement increased). The effect of treatment on change in serum D3 concentration was modified only by body weight (−0.33 nmol/L per kg of weight; P  = 0.01). Conclusions: Among older adults, 2 years of 2000 IU/day vitamin D3 led to similar mean increases in serum D3 and 25(OH)D. Unlike the serum 25(OH)D response, the serum D3 response to supplementation did not depend on baseline vitamin D status. The serum vitamin D concentration may be an additional, valuable marker of exposure to vitamin D during supplementation. Funding Sources: NIDDK NIH ODS NHLBI.